Diagnosis and Treatment of Trigger Finger in Brazil - A Cross-Sectional Study - Paulo Henrique Jeronimo da Silva; Vinícius Ynoe de Moraes; Nicolau Granado Segre; Edson Sasahara Sato; Flávio Faloppa; João Carlos Belloti (Revista Brasileira de Ortopedia, 2021)
Abstract Objective The present paper aims to evaluate the therapeutic planning for trigger finger by Brazilian orthopedists. Methods This is a cross-sectional study with a population composed of participants from the 2018 Brazilian Congress on Orthopedics and Traumatology (CBOT-2018, in the Portuguese acronym), who answered a questionnaire about the conduct adopted for trigger finger diagnosis and treatment. Results A total of 243 participants were analyzed, with an average age of 37.46 years old; most participants were male (88%), with at least 1 year of experience (55.6%) and from Southeast Brazil (68.3%). Questionnaire analysis revealed a consensus on the following issues: diagnosis based on physical examination alone (73.3%), use of the Quinnell classification modified by Green (58.4%), initial nonsurgical treatment (91.4%), infiltration of steroids combined with an anesthetic agent (61.7%), nonsurgical treatment time ranging from 1 to 3 months (52.3%), surgical treatment using the open approach (84.4%), mainly the transverse open approach (51%), triggering recurrence as the main nonsurgical complication (58%), and open surgery success in > 90% of the cases (63%), with healing intercurrences (54%) as the main complication. There was no consensus on the remaining variables. Orthopedists with different practicing times disagree on treatment duration (p = 0.013) and on the complication rate of open surgery (p = 0.010). Conclusions Brazilian orthopedists prefer to diagnose trigger finger with physical examination alone, to classify it according to the Quinnell method modified by Green, to institute an initial nonsurgical treatment, to perform infiltrations with steroids and local anesthetic agents, to sustain the nonsurgical treatment for 1 to 3 months, and to perform the surgical treatment using a transverse open approach; in addition, they state that the main nonsurgical complication was triggering recurrence, and report open surgery success in > 90% of the cases, with healing intercurrences as the main complication.